Development of stop motion-based macromedia flash to strengthen nautical character - Sunyoto, Tarissa Aditya Berlin; Mujahidin, Muhammad Diwanul; Imron, Ali (JIPSINDO, 2024)
The massive development of digital technology has changed aspects of human life, including education. Thus, in the face of the digital era, technology is paramount to increasing learning effectiveness. One of the integrated technologies is stop motion-based Macromedia Flash, a learning media that offers interactive learning experiences through moving animations. This research aims to develop student-centred aspects of feasibility, practicality, and effectiveness based on constructivism theory. The research uses the ADDIE model development method. The results of media and material validation on the stop motion-based Macromedia Flash show that this media is declared "feasible" with an overall score of 83%. Regarding practicality and efficiency, the stop motion-based Macromedia Flash achieved a score of 104% (very feasible) and 60.4% (high), respectively. In addition, the use of this media supports constructivism theory by demonstrating its activeness in social studies learning. This not only improves learners' understanding of the material but also has the potential to enrich their nautical character development.